Windows Server 2003 Networking Recipes - Allen, Robbie (Apress, 2013)
This book contains more than 200 recipes that address many of the “How do I . . .?” questions that you could pose about Windows networking. It is a straightforward reference for a variety of tasks, ranging from handling everyday chores to solving more specialized problems. Windows Server 2003 Networking Recipes will be a great addition to your technical library